Influence Satisfaction and Trust to Loyalty Customer in Use Product Superior Micro at PT. Bank Rakyat Indonesia Tbk (Persero) - Nurul Fadilah Aswar; Andi Rifqah Purnama Alam (CV. Sakura Digital Nusantara, 2023)
This study aims for know influence satisfaction and trust to loyalty customers in use product superior micro (Kupedes) at PT. Bank Rakyat Indonesia Tbk (Persero) A. P. Pettarani Unit Office. As for the population study is PT Bank Rakyat Indonesia Tbk (Persero) customers A. P. Pettarani Unit Office which uses product superior micro (Kupedes). Sample finally obtained is 100 respondents. Data analysis used analysis track (Path Analysis) using Statistical Product Standard Solution (SPSS 25). The results of data analysis show that variable satisfaction influential significant to trust with mark X1 significanct of 0.0001 <0.05. However, variables satisfaction no there is influence significant to loyalty with mark X1 significance of 0.232>0.05. Variable trust there is influence significant to loyalty with mark X2 significance of 0.0001 <0.05. Then analysis satisfaction through trust to loyalty is known influence given directly of 0.126, meanwhile influence no direct X1 through X2 to Y of 0.581, which means that mark influence no direct more big compared to with mark influence direct. So that can concluded that in a manner no direct satisfaction through trust have influence significant to loyalty.